Essentialist traps and how to avoid them - Nicolas Femia (Educare)
Through the monolingual bias and essentialist understandings of language in education, multilingual youth across the globe have consistently been portrayed as deficient based on their linguistic practices. Deficit approaches in education stem from a colonial project meant to silence the voices and erase the experiences of the Other, and although there is a long tradition of pedagogies that try to counteract this form of discrimination, these attempts are typically built on principles and assumptions that reproduce essentialism and dynamics of marginalization. In this position paper, I argue that it is necessary for educators to engage with non-essentialist understandings of language and multi-sided perspectives on multilingualism to develop pedagogies that are empowering for multilingual youth in Sweden. By engaging with the decolonial notion of linguistic citizenship, educators in Sweden can allow fluid understandings of multilingualism to enter the classroom, creating spaces for socio-political participation and dialogue at the margins of institutional arenas in which language can be negotiated. This measure creates opportunities for empowerment for all students, engaging them in the reconstruction of language and giving voice to stories that would otherwise remain silent.